Time to viral load suppression and its predictors among people living with HIV on antiretroviral therapy in Gebi Resu zone, Afar Region, Ethiopia, 2023 - Chirnet, Anteneh Tefera; Habtewold, Ephrem Mannekulih; Aman, Haji; Wakwoya, Elias Bekele; Workie, Sewnet Getaye (Frontiers in Public Health, 2024)
Objective This study aimed to estimate the time to viral load suppression and identify its predictors among HIV patients receiving antiretroviral therapy (ART) in the Gebi Resu zone, Afar Region, Ethiopia, 2023. Setting The study was conducted at public health facilities in the Gebi Resu zone of the Afar region. Study design This study is a facility-based, retrospective follow-up study. Study participants This study included 298 people living with HIV who were receiving ART services at selected health facilities in the Gebi Resu zone. Data were collected by reviewing patient records using a structured checklist. Bivariate and multivariate Cox regression analyses were conducted to assess the relationship between variables and control for confounders. Results The incidence rate of viral load suppression was 9.46 per 100 person-months. The median time to viral load suppression was 7.7 months, with an interquartile range of 3.8 months (IQR = 6.47–10.27). Patients at clinical stages 3 and 4 [AHR = 0.67, 95%CI (0.47, 0.96)], those who received cotrimoxazole prophylaxis therapy [AHR = 1.47, 95%CI (1.12, 1.92)], and patients with poor drug adherence [AHR = 0.40, 95%CI (0.18, 0.90)] were significantly associated with time to viral load suppression among people on antiretroviral therapy. Conclusion The time to viral load suppression and the median time to viral load suppression among people living with HIV on ART were shorter than those observed in many developing and developed countries. Clinical stage, cotrimoxazole prophylaxis therapy, and drug adherence were significant predictors of viral load suppression.